2020
DOI: 10.3390/ijerph17165973
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown: Housing Built Environment’s Effects on Mental Health

Abstract: Since the World Health Organization (WHO) declared the coronavirus infectious disease 2019 (COVID-19) outbreak a pandemic on 11 March, severe lockdown measures have been adopted by the Italian Government. For over two months of stay-at-home orders, houses became the only place where people slept, ate, worked, practiced sports, and socialized. As consolidated evidence exists on housing as a determinant of health, it is of great interest to explore the impact that COVID-19 response-related lockdown measures have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
305
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(339 citation statements)
references
References 51 publications
24
305
1
9
Order By: Relevance
“…Studies have shown that housing conditions are even more predictive than the degree of dependency in predicting abandonment of the home and institutionalization ( 34 ). In line with Amerio et al ( 21 ), our results point to a greater presence of negative feelings during quarantine in participants who do not have open spaces at home. It has been pointed out that housing design strategies should focus on larger living spaces and visible and accessible green areas ( 20 , 21 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Studies have shown that housing conditions are even more predictive than the degree of dependency in predicting abandonment of the home and institutionalization ( 34 ). In line with Amerio et al ( 21 ), our results point to a greater presence of negative feelings during quarantine in participants who do not have open spaces at home. It has been pointed out that housing design strategies should focus on larger living spaces and visible and accessible green areas ( 20 , 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…Previous works have shown that visual contact with nature has a reliable effect in physiological relaxation ( 18 , 19 ), but the strict confinements due to the COVID-19 crisis have clearly shown the need to direct outdoor exposure and its potential implication for psychological, social and physical health ( 20 ). Amerio et al ( 21 ) studied the relation between mental health and housing conditions, including housing dimension, presence or absence of liveable open space and quality of views, in 8,177 students from a university institute in Milan, Northern Italy, after 3 weeks of strict lockdown. Compared to students with absent to moderate depressive symptoms, students with moderate–severe and severe depressive symptoms lived in smaller apartments, with unusable balconies and poor-quality views from their apartments.…”
Section: Introductionmentioning
confidence: 99%
“…As various studies on psychological and mental effects related to confinement and the built environment have confirmed [64], there is a direct relationship between poor or bad quality housing and its services or equipment, with a more negative spatial perception, and even a greater potential for development or worsening of mental health [65], and vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies conducted on people's mental health during lockdown or isolation reported restriction of movement showed that when people are restricted to a certain kind of environment, their mental health is adversely affected [10][11][12][13] . Historically, quarantine has been related to psychological outcomes such as anxiety, depression, panic, irritability, somatic disorder, and insomnia 14 .…”
Section: Introductionmentioning
confidence: 99%